(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article provides a comprehensive analysis of the main categories of pedagogy – education, upbringing, and teaching – from the perspective of modern pedagogical theories. The study examines competency-based education, the constructivist learning model, and the processes of clinical thinking formation. The integrative nature of pedagogical categories in medical education, namely the combination of knowledge, practical skills, and professional values, is substantiated. The results indicate that the integration of pedagogical categories with modern approaches significantly enhances the effectiveness of medical education.